EVALUATION OF THE IMPLEMENTATION OF SCIENCE LITERACY-BASED LEARNING IN MADRASAH IBTIDAIYAH - Herianingtyas, Nur Luthfi Rizqa; Wafiqni, Nafia (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
This study was conducted to evaluate the implementation of science literacy-based learning in primary schools. The evaluative quantitative investigation used Stake's Countenance Model to measure the implementation of authentic assessments, including three critical stages, namely (1) Antecedent, (2) Process, and (3) Outcomes. A purposive sampling technique was used to select 20 Islamic Elementary Schools (IES) in West Java that participated in the Indonesian Madrasah Competency Assessment (IMCA) result follow-up training programs. Furthermore, data collection methods included observation, interviews, and questionnaires, which were analyzed using a percentage-based analytical approach. This allowed direct understanding into the information disclosed and the identification of specific aspects of the studied problem. Observation and interview data were analyzed using an interactive model, including data collection, display, and conclusion. The results showed that several aspects did not achieve the 100% standard. Planning (Atencedents) in the “Not Good” category with a percentage of 61.40%, while Implementation (Transaction) and Results (Outcomes) stages obtained 70.17% and 52.36% in the “Enough” and the “Very Not Good” categories.